An investigation of polymersomes as nanocarriers for drug delivery - Ou, Yi Hsuan (2016)
Considering its good stability and tunability of physicochemical properties, polymersomes have been explored as novel nanocarriers for many different biomedical applications. The poly(butadiene)-b-(ethylene oxide) (PBd-b-EO) is one of the popular choices for forming these self-assembled polymersomes. The aim of this study is to evaluate the characteristics, loading capacity and release profile of polymersomes synthesized from this copolymer with different molecular weights through two common formulation methods (co-solvent method and thin-film rehydration). Three copolymers of different molecular weight were used in this study to determine its effects on the properties of the polymersomes, and these vesicles were characterized by Dynamic Light Scattering (DLS) and cryogenic Transmission Electron Microscopy (Cryo-TEM). Their dual loading capacity was demonstrated, and in vitro release profile was established with Dexamethasone. The PBd(1.9)-b-EO(0.9) polymersomes from thin-film rehydration were found to demonstrate the sustained release over the course of 9 days, with reasonable drug quantity (0.07 to 0.32% w/w). Their long-term stability was observed over the course of 2 months under storage condition (4oC) which further suggest the vast potential of this polymersome as drug carrier in development of sustained release drug delivery.